Pelanggaran kode etik profesi hukum: peran mahasiswa hukum dan manipolitik - nasrullah, Nasrullah (Maliki Interdisciplinary Journal, 2025)
In maintaining the integrity and dignity of the legal profession and preventing political intervention in law enforcement, the code of ethics of the legal profession serves as a moral guideline that directs legal actors, such as advocates, judges, prosecutors, and notaries, to act in accordance with the principles of justice, honesty, and transparency. In this case, the code of ethics is not only a written rule but also a moral commitment to maintain the integrity and dignity of the legal profession. However, various problems are often encountered when implementing the code of ethics, such as low moral integrity and autonomy of legal actors. Violation of the code of ethics can reduce public trust in the legal system and the wisdom of political manipulation practices. Therefore, in order to implement the code of ethics properly, internal law enforcement agency reform is very important. Therefore, the code of ethics of the legal profession plays an important role in creating a fair legal system free from political interference. The code of ethics of the legal profession is very important to maintain the justice and integrity of the legal system and prevent political manipulation. Advocates, judges, and prosecutors are held by this code of ethics to act honestly, transparently, and responsibly. Conversely, conflicts of interest and low integrity often cause difficulties in implementing the code of ethics. Those who violate the code of ethics can damage public trust in legal institutions and the acceptance of political manipulation methods. Therefore, to ensure the effective implementation of the code of ethics, law enforcement agencies must be reformed. Therefore, the code of ethics of the legal profession not only provides regulations, but also helps build a fair legal system free from political influence.